2018
DOI: 10.1016/j.scitotenv.2018.06.313
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic particles in the stomach contents and liver of the freshwater fish Squalius cephalus

Abstract: Anthropogenic particles (APs) are a very broad category of particles produced directly or indirectly by human activities. Their ingestion by biota is well studied in the marine environment. In contrast, studies on AP ingestion in wild freshwater organisms are scarce despite high contamination levels in some rivers and lakes. In this study, we aimed to evaluate the ingestion of APs and the possible occurrence of APs in the liver and muscle of a freshwater fish, Squalius cephalus, from the Parisian conurbation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 65 publications
5
74
3
Order By: Relevance
“…This result is higher in comparison with fish collected from other European rivers (e.g. Sanchez et al 2014;Collard et al 2018;Roch et al 2019); however, different methods were used in measuring the occurrence of MPs in fish. Although visual identification of MPs following Nor and Obbard (2014) criteria can be used (e.g.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This result is higher in comparison with fish collected from other European rivers (e.g. Sanchez et al 2014;Collard et al 2018;Roch et al 2019); however, different methods were used in measuring the occurrence of MPs in fish. Although visual identification of MPs following Nor and Obbard (2014) criteria can be used (e.g.…”
Section: Discussionmentioning
confidence: 70%
“…Although rivers seem to be the main source of MPs in marine ecosystems, current knowledge about freshwater contamination is scarce (Wagner et al 2014). Most papers have focused on large rivers that include the Seine, Yangtze and Thames (Zhang et al 2015;Collard et al 2018;Horton et al 2018). However, Sanchez et al (2014) and Slootmaekers et al (2019) showed that smaller streams may also contain less intense concentrations of MPs.…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics were present in 100% of the fish. Comparably high prevalence of microplastics in freshwater fish has been found in several rivers in the midwestern U. only 9% of gudgeon in Belgian rivers had microplastics (Slootmaekers et al 2019), 25% of gudgeon in French rivers (Sanchez et al 2014), 25% of chub (Squalius cephalus) in a river near Paris (Collard et al 2018), and 33% of roach in the River Thames, UK (Horton et al 2018). It is unclear whether the wide range reported for the prevalence of microplastics is due to ecological (riverine vs. lacustrine), watershed land-use, or cultural differences.…”
Section: Discussionmentioning
confidence: 87%
“…The potential of microplastics translocation to the fish tissue may increase with a reduction in the size of plastic particles. As the finding of Collard et al (2018), microplastic particles can be translocated into the liver of wild freshwater fish, while no microplastics were detected in muscle tissue. Polystyrene microplastics accumulated in gut > gills > liver and brain of Oreochromis niloticus (Ding et al 2018).…”
Section: Size Of Ingested Microplasticsmentioning
confidence: 83%